Shadows in winter : a memoir of love and loss - Fishbane, Eitan P., 1975- (Library of modern Jewish literature., 2011)
In March 2007, Leah Fishbane, a promising young graduate student in the prime of her life, was struck down suddenly with an undiagnosed brain tumor. In this deeply evocative memoir, written during the dark time of the first year following Leah's death, her husband Eitan gives voice to the overwhelming power of grief and to the deep love that underlies such pain. He tells the story of his efforts to be a good father to his grieving four-year-old child and of his discovery of himself as a parent in ways he had not known before. Along this path, Fishbane asks fundamental questions about the meaning of death and life, about the place of God and faith in the experience of tragedy, reflecting on what it means to live with loss. The result is a poetic testament that will resonate with countless mourners and their loved ones. In giving honest expression to emotions that are at once particular and universal, Shadows in Winter offers a luminous window of comfort and hope to those battling the devastation of loss.